The Implications of Capital Structure on Financial Performance in Consumer Goods Manufacturing Companies: Empirical Evidence from PT ICBP Tbk - Abdul Rosyid (CV. Era Digital Nusantara, 2025)
This study aims to empirically examine the effect of capital structure on the financial performance of PT Indofood CBP Sukses Makmur Tbk (ICBP) from 2019 to 2023. Capital structure is proxied by the Debt to Equity Ratio (DER), while financial performance is measured by Return on Equity (ROE). A quantitative method with a descriptive-verificative approach was employed, using secondary data sourced from annual financial statements on the Indonesia Stock Exchange. The results of the simple linear regression analysis indicate that capital structure has a significant negative effect on financial performance (t count 3.874 > t table 2.571; sig. 0.002 < 0.05). These findings suggest that an increase in the proportion of debt within the capital structure tends to decrease the efficiency of the company's financial performance. The implications of this study suggest that management should optimize the capital composition to minimize interest expenses that could erode profitability.